PAPILLON–LEFEVRE SYNDROME: A COMBINED APPROACH FROM THE DERMATOLOGIST AND DENTIST – A CLINICAL PRESENTATION - Muppa, Radhika (Medknow Publications & Media Pvt Ltd, 2011)
Papillon–Lefevre syndrome (PLS) is a rare disease characterized by skin lesions, which includes palmar-plantar hyperkeratosis and hyperhidrosis with severe periodontal destruction involving both the primary and the permanent dentitions. It is transmitted as an autosomal-recessive condition, and consanguinity of parents is evident in about one-third of the cases. This paper describes a 13-year-old male patient who presented to the department of pedodontics, with rapidly progressing periodontitis. A general physical examination revealed scaling on the hands and feet, which had been medically diagnosed as PLS. The incidence of this rare entity is increasing in the recent times, which is associated with irreparable periodontal destruction at an early age, with not so prominent skin lesions in some cases. In such instances, the dentist has a more important role in diagnosing, treatment planning and preservation of the periodontal tissues and, at the same time, referring for the treatment of the skin lesions. This paper emphasizes the combined effort of the two specialities in order to maintain skin as well as dental conditions in health by early intervention and a synergistic treatment approach.